The effect of dental plaque level and self-performed oral hygiene on periodontal status: a cross-sectional study in Brazilian Indigenous - dos Santos, Jean Nunes; Coelho, Tayane da Rocha Costa; Cury, Patricia Ramos; Pinto Filho, Jorge Moreira; Araujo, Nara Santos (Journal of Health & Biological Sciences, 2021)
Objective: This study evaluated the associations of periodontal status with dental plaque index and frequency of toothbrushing and flossing in Kiriri Brazilian Indigenous people. Methods: Gingival bleeding, periodontal clinical attachment level, and dental plaque index were clinically evaluated in 204 adult Brazilian indigenous. They were categorized as healthy, gingivitis, or periodontitis. Sociodemographic data and oral hygiene habits were registered. Bivariate and logistic regression analyses were performed (p≤0.05). Results: Gingivitis [odds ratio (OR): 2.83; 95% confidence interval (CI), 1.52–5.25; p=0.001] and periodontitis (OR: 6.88; 95%CI, 1.44–32.78; p=0.02) were associated with plaque index level, but not with toothbrushing or flossing frequency (p ≥0.55). Conclusion: Gingivitis and periodontitis were associated with higher plaque index, but not with the frequency of toothbrushing and flossing. To enhance this population’s periodontal health, a prevention program focused on improving the quality of self-performed oral hygiene should be planned and implemented.